Risk Factors Leading to Acute Decompensation of Chronic Heart Failure in Patients Presenting to a Tertiary Care Hospital, Islamabad, Pakistan - Muhammad Said Nawaz, Kalsoom Bibi, Syed Nasir Ali Shah, Zarak Khan, Muhammad Ilyas, Nouman Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: To determine the risk factors leading to acute decompensation of chronic heart failure in patients presenting to a tertiary care hospital, Islamabad, Pakistan Methodology: Study was conducted at Pakistan Institute of Medical Sciences, Cardiology department, Islamabad, Pakistan, 164 chronic heart failure patients aged ≥18 years; diagnosed with CHF from both genders were included. Patients with sudden onset of disease and unstable vital signs, impaired mobility; diagnosis with major depression or those having cognitive functioning disorder were excluded from study.Medical records were analyzed for the patient’s chronic heart failure risk factor profile i.e., history of diabetes, hypertension, hyperlipidemiaand smoking. Details of the coronary angiogram, laboratory investigations, and metabolic and cardiac biomarker were noted. Data was entered and analyzed using statistical package for social sciences (SPSS) version 2.0. P< 0.05 will be considered as significant. Results: In study analysis it was found that out of total 164 participants, study included 78 males (47.6%) and 86 females (52.4%). out of which 157 (95.7%) were having history of hypertension and 85 (51.8%) were found to be having history of diabetes. Participant included in study who used to smoke were 92 (56.1%), patients having dyslipidemia were found to be 85 (51.8%) and 85 (51.8%) were obese. Out of all patients 157 (95.7%) were found to be having a sedentary life, while 19 (8.5%) participants have developed new ischemia. Out of all participants 93 (56.71%) were found to be having ECG changes and 72 (43.9%) were found to have cardiac enzyme changes. Mean age of participant was found to be 59.51±45.54. Mean HB level was found to be 12.8±1.8 and mean respiratory rate was found to be 19.12 ±3.4. Mean pulse was found to be 94.7±3.4. Mean BP was found to be 118.22±10.7.